Desarrollo de un curso virtual para la alfabetización digital de los padres de familia, como estrategia para apoyar el aprendizaje en la asignatura de estudios sociales, de los alumnos del séptimo año de educación general básica paralelo A de la unidad educativa Lauro Damerval Ayora Nº1 de la ciudad de Loja, período 2014-2015 - Oviedo Sandoval, Wilman Enrique (2016)
This present research work was made on the detected problem about digital illiteracy and lack of support for students in the seventh year of General Basic Education parallel "A" at Lauro Damerval Ayora Number 1 School of the city Loja, in the research tasks on internet about Social Studies subject, for the parents. For the development was used the eclectic methodology for virtual course which allowed interact directly with the parents, the teacher and students that helped with the collection of data through the application of a survey and an interviews to determine the information that were used to help to the virtual course’s development, also with the completion of each of its phases could achieve the objectives proposed in this research work. Finally the use of the virtual course allows and encourages support learning in the Social Studies subject for the parents to the student in the seventh year of General Basic Education at Lauro Damerval Ayora N°.1 School, besides this course helps to the parents become an advisor or tutor to their children at the moment of performing the tasks or homework from internet that teacher sent to the children and teacher can grade the parameters while parents learn and become familiar with the use of digital tools.